2018
DOI: 10.1111/cup.13273
|View full text |Cite
|
Sign up to set email alerts
|

Scleroderma‐like skin changes induced by checkpoint inhibitor therapy

Abstract: Checkpoint inhibitors have emerged as beneficial therapies in many different types of malignancy. The most common toxicities of checkpoint inhibitors are immune-related adverse events (irAEs). As clinical experience with these agents increases, more irAEs have been described. We report a case of scleroderma-like skin changes induced by checkpoint inhibitor therapy. A 61-year-old man was treated with nivolumab for oligometastatic renal cell carcinoma. He initially tolerated the therapy well, but after 16 treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 12 publications
0
33
0
Order By: Relevance
“…More recently, anticancer immunotherapy using immune checkpoint inhibitors has been shown to trigger autoimmunity, and a few cases of scleroderma have been reported in the literature (5557, 140). In this context, the complexity of the interplay between anti-cancer pre-existing autoimmunity, genuine paraneoplastic syndromes and the effects of immune system stimulation by biologics is striking, and strengthens the relationships between SSc and malignancy.…”
Section: Shared Mechanisms In Cancer and Systemic Sclerosismentioning
confidence: 99%
“…More recently, anticancer immunotherapy using immune checkpoint inhibitors has been shown to trigger autoimmunity, and a few cases of scleroderma have been reported in the literature (5557, 140). In this context, the complexity of the interplay between anti-cancer pre-existing autoimmunity, genuine paraneoplastic syndromes and the effects of immune system stimulation by biologics is striking, and strengthens the relationships between SSc and malignancy.…”
Section: Shared Mechanisms In Cancer and Systemic Sclerosismentioning
confidence: 99%
“…Scleroderma is an even rarer event that has been reported following PD-1 blockade. These cases involved typical skin tightness of the hands and feet and dermal sclerosis on histology [37,38] . The underlying mechanism for this is unknown, it is reported that TGFβ cascade is activated within the skin after treatment with anti-PD-1, which results in fibrosis [37] .…”
Section: Sclerodermamentioning
confidence: 99%
“…Alopecia areata (AA) is an autoimmune disease that results in unpredictable, patchy hair loss. AA is reported in 1-2% cancer patients receiving immune checkpoint inhibitor therapy [38,39] . AA caused by checkpoint inhibitor therapy shares several features with the classical AA.…”
Section: Alopecia Areatamentioning
confidence: 99%
“…Some patients experienced systemic sclerosis [7] or scleroderma-like reaction [63–65], all presenting with skin thickening but only one with associated recent Raynaud phenomenon. None tested positive for specific autoantibodies.…”
Section: Other Systemic Manifestationsmentioning
confidence: 99%